It worked for me in life and leadership - Powell, Colin (New York Harper, 2012)
It Worked for Me is filled with vivid experiences and lessons learned that have shaped the legendary public service career of the four-star general and former Secretary of State Colin Powell. At its heart are Powell's short but sweet rules-among them, "Get mad, then over it" and "Share credit"- are illustrated by revealing personal stories that introduce and expand upon his principles for effective leadership: conviction, hard work, and in life, Powell writes, "it's about how we touch and are touched by the people we meet. Its all about the people." A natural storyteller, Powell offers warm and engaging parables with wise advice on succeeding in the workplace and beyond. "Trust your people," he counsels as he delegates presidential briefing responsibilities to two junior State Department desk officers. "Do your best-someone is watching," he advises those just starting out, recalling his own teenage summer job mopping floors in a soda bottling factory. Powell combines the insights he has gained serving in the top ranks of the military and in our presidential administrations with the lessons he's learned from his immigrant-family upbringing in the Bronx, his training in the ROTC, and his growth as an Army officer. The result is a powerful portrait of leader who is reflective, self-effacing, and grateful for the contributions of everyone he works with.
Keywords: Powell, Colin L. African American generals --Biography. Leadership --United States